Precautionary allergen labelling: perspectives from key stakeholder groups. Issue 9 (25th June 2015) - DunnGalvin, A.; Chan, C.‐H.; Crevel, R.; Grimshaw, K.; Poms, R.; Schnadt, S.; Taylor, S. L.; Turner, P.; Allen, K. J.; Austin, M.; Baka, A.; Baumert, J. L.; et al.
Abstract Precautionary allergen labelling (PAL) was introduced by the food industry to help manage and communicate the possibility of reaction from the unintended presence of allergens in foods. However, in its current form, PAL is counterproductive for consumers with food allergies. This review aims to summarize the perspectives of all the key stakeholders (including clinicians, patients, food industry and regulators), with the aim of defining common health protection and risk minimization goals. The lack of agreed reference doses has resulted in inconsistent application of PAL by the food industry and in levels of contamination that prompt withdrawal action by enforcement officers. So there is a poor relationship between the presence or absence of PAL and actual reaction risk. This has led to a loss of trust in PAL, reducing the ability of consumers with food allergies to make informed choices. The result has been reduced avoidance, reduced quality of life and increased risk‐taking by consumers who often ignore PAL. All contributing stakeholders agree that PAL must reflect actual risk. PAL should be transparent and consistent with rules underpinning decision‐making process being communicated clearly to all stakeholders. The use of PAL should indicate the possible, unintended presence of an allergen in a consumed portion of a food product at or above any proposed action level. This will require combined work by all stakeholders to ensure everyone understands the approach and its limitations. Consumers with food allergy then need to be educated to undertake individualized risk assessments in relation to any PAL present.